A Systematic Literature Review on The Economic Impact of Local Communities on High Priority Destinations in the Indonesian area - Bagas Anggara; Budiman; Rizki Sumardani; Claudia Dwi Martina (Universitas Muhammadiyah Jember, 2025)
This study aims to analyze the economic impact of community-based tourism on Indonesia’s five super-priority destinations—Borobudur, Mandalika, Labuan Bajo, Lake Toba, and Likupang—using a Systematic Literature Review (SLR) approach. The findings indicate that the development of community-based tourism significantly contributes to local income growth, job creation, and the strengthening of micro, small, and medium enterprises (MSMEs). Beyond its economic influence, tourism also reinforces cultural identity, encourages social participation, and enhances quality of life through improved access and community awareness. However, several challenges remain, including the dominance of political and economic interests, limited human resource capacity, lack of basic infrastructure, unequal benefit distribution, and the risks of environmental degradation and cultural commodification. The study highlights that the success of super-priority destination management depends not only on physical development but also on local economic empowerment and the adoption of sustainable tourism principles. Through a pentahelix collaboration among government, local communities, academia, businesses, and media, tourism management can become more inclusive, equitable, and sustainable.